Efektivitas Model Pemeblajaran CORE (Connecting, Organizing, Reflecting, Extending) Dengan Strategi Student Facilitator And Explaining Terhadap Pemahaman Konsep Matematis Siswa - intan tri utami; Lisma Dian Kartika Sari; Miftahus Surur (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2023)
AbsrtactMathematics is one of the compulsory subjects taught at all levels of education. a model is neededto support students' needs to improve students' understanding of concepts. The CORE learningmodel with the Student facilitator and explaining strategy is very good in improving students'understanding of mathematical concepts. The purpose of this study was to determine theeffectiveness of the CORE model with a student facilitator and explaining strategy on students'understanding of mathematical concepts. This study uses a quantitative method with a quasiexperimental approach and a non-equivalent control group design. the author conducted a test ofvalidity, normality, homogeneity and reliability of the test to determine the correctness andsuitability of the instrument used. From the calculation results, the results of the test have a validvalue and have a normal distribution. For the homogeneity and reliability test, all items werehomogeneous. The calculation using the Crombach alpha reliability test was obtained for all itemsmore than 0.05, so all items on the test were appropriate or reliable. It is known that the results ofthe t-test analysis in the experimental class have an average value (mean) of 63.7 post-test andpre-test of 47.5, the increase in the average result is known to be 16.2 for all test results. Inaddition, from the results of the percentage of the effectiveness of the model category, the result isa value of 63.75. So, from these results the category of effectiveness of the learning model isincluded in the category of quite effective. Keywords: Effectiveness, CORE Model and Student Facilitator and Explaining Strategy, Understanding Mathematical Concepts